Impact of salinity on the socio-environmental life of coastal people of Bangladesh. - Mustari, Sohela; Karim, A.H.M Zehadul (2012)
Based on 1st author’s own participation and informal discussion with the inhabitants of coastal areas, these researchers attempt to know the impact of salinity on the socio-environmental life of coastal people. Bangladesh is a country which is slopped gently from the north to the south, where it meets the Bay of Bengal at its southern end. Because of its critical geographical location, almost every year the southern coastal areas face various kinds of natural disasters, such as cyclones, flood, soil erosion, tidal surge, sea level rise and so on. All these natural disasters bring saline water with them from the sea, which creates a new dimension of natural disaster. This Salinity is very crucial in terms of its impact on the socio-ecological life of the local people. It is destroying the natural characteristics of coastal soil and water. Moreover it is causing damage to agriculture, bio-diversity, fresh water and its resources which are absolutely degrading the quality of local people’s life. This paper therefore is designed to know about the overall impact of salinity on the socio-environmental lives of coastal people. Key words: salinity, sustainable development, coastal areas, Bangladesh, socio-environmental life.